Evaluation of 2 Ultraviolet-C Light Boxes for Decontamination of N95 Respirators - Jennifer Cadnum; Basya Pearlmutter; Daniel Li; Annette Jencson; Jacob Scott; Ian Charnas; Curtis Donskey (Case Western Reserve University, 2021)
Background:  Ultraviolet-C (UV-C) light devices are effective in reducing contamination on N95 filtering facepiece respirators.  However, limited information is available on whether UV-C devices meet the Food and Drug Administration's (FDA) microbiological requirements for Emergency Use Authorization (EUA) for respirator bioburden reduction.  Methods:  We tested the ability of 2 UV-C light boxes to achieve the 3-log10 microorganism reductions required for EUA for reuse by single users.  Whole 3M 1860 or Moldex 1513 respirators were inoculated on the exterior facepiece, interior facepiece, and internal fibers with bacteriophage MS2 and/or 4 strains of bacteria and treated with UV-C cycles of 1 or 20 minutes.  Colorimetric indicators were used to assess penetration of UV-C through the respirators.    Results:  For 1 UV-C box, a 20-minute treatment achieved the required bioburden reduction for Moldex 1513 but not 3M 1860 respirators.  For the second UV-C box, a 1-minute treatment achieved the required bioburden reduction in 4 bacterial strains for the Moldex 1513 respirator.  Colorimetric indicators demonstrated penetration of UV-C through all layers of the Moldex 1513 respirator but not the 3M 1860 respirator.  Conclusions:  Our findings demonstrate that UV-C box technologies can achieve bioburden reductions required by the FDA for EUA for single users but highlight the potential for variable efficacy for different types of respirators.